Exploring Rice Marketing Strategies: A Case Study of Toili Sub-district, Banggai Regency - Muala, Bakri (LifeSciFi, 2023)
Agricultural marketing encompasses the movement of goods, ownership transfer, and the creation of utility in time, place, and form. Marketing institutions execute functions to facilitate this process. This research aims to understand the rice marketing margin. The respondents in this study are rice farmers in the Toili sub-district of Banggai Regency. The selection of respondents was deliberate, considering that the Toili sub-district is a center of rice production in Banggai Regency. The data analysis used quantitative methods to calculate the marketing margin. The research results indicate that the rice marketing channels from farmers are directed to both collector traders and directly to consumers. The marketing margin for rice is Rp. 1000 Indonesian Rupiah, where the selling price from rice farmers to collector traders is Rp. 13,000 and the resale price to consumers is Rp. 14,000. The research findings reveal that the efficiency of the rice marketing channel in the Toili sub-district has a value of 28.57%, which is below the threshold of 50% indicating efficient marketing channels.